2021
DOI: 10.9734/jerr/2021/v20i417290
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Water Quality Indexes for an Inland River

Abstract: The present study assessed water quality parameters and attempts to compare four different Water Quality Indexes (WQIs) for consistency, similarity and reliability in assessing the water quality of river Benue -an inland river- under wet and dry seasons. The results demonstrate that River Benue is continually being polluted in both dry and wet seasons by different sources, particularly domestic sewage and storm runoffs from farmlands. The quality of the water generally exceeded physiochemical and microbiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…Mean Nitrate values of all samples obtained from the various locations was 8.52±3.40 and though within the maximum limits specified by WHO (2011) of 50mg/L, there is an obvious increase in their concentrations when compared to previous research. This research agrees with the findings of Kondum et al, [15] in the same study area, who reported nitrate levels of between 8.34±0.30 and 14.69±1.35 mg/L. The nitrate values here however vary with the earlier findings of Okenyi et al, [16] who reported very low values of 2.0 and 2.7 mg/L.…”
Section: Discussionsupporting
confidence: 92%
“…Mean Nitrate values of all samples obtained from the various locations was 8.52±3.40 and though within the maximum limits specified by WHO (2011) of 50mg/L, there is an obvious increase in their concentrations when compared to previous research. This research agrees with the findings of Kondum et al, [15] in the same study area, who reported nitrate levels of between 8.34±0.30 and 14.69±1.35 mg/L. The nitrate values here however vary with the earlier findings of Okenyi et al, [16] who reported very low values of 2.0 and 2.7 mg/L.…”
Section: Discussionsupporting
confidence: 92%